The crystal structure of poly(ethylene furanoate). (12th October 2016) - Mao, Yimin; Kriegel, Robert M.; Bucknall, David G.
Abstract: The crystal structure of poly(ethylene furanoate) (PEF) has been determined using X-ray fiber diffraction (XRFD) combined with molecular modeling. Analysis of the XRFD data suggested the space group was P21, with a monoclinic unit cell where a  = 5.784 Å, b  = 6.780 Å, c  = 20.296 Å, and γ = 103.3°, giving a calculated unit cell density of the crystal phase was 1.562 g/cm 3 . The repeating unit consisted of two monomers related to each other by a 21 screw axis. It was also shown that two PEF chains were included in each unit cell, with the center-chain being staggered with respect to the corner-chain. Polymer chains were found to be near planar, although careful evaluation showed that the best fit with the data required the cell to contain a mixture of 3/12 and 5/12 center-chain-staggering. Graphical abstract: Comparison of experimental fiber diffraction (upper-left and lower-right) and simulated pattern (upper-right and lower-left) of poly(ethylene furanoate). Highlights: Crystal structure of poly(ethylene furanoate) was determined by fiber diffraction. The proposed structure possessed a monoclinic unit cell and P21 space group. Chain staggering and bending was observed in PEF unit cell. The crystal density of the PEF was calculated to be 1.562 g/cm 3 .